2011
DOI: 10.1111/j.1740-0929.2010.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of feeding systems: feed cost, palatability and environmental impact among hay‐fattened beef, consistent grass‐only‐fed beef and conventional marbled beef in Wagyu (Japanese Black cattle)

Abstract: The objective of this article is to compare feed cost, palatability and environmental impacts among feeding systems of high concentrate (HC), high hay (HH) and grass-only-fed (Gof) groups. Feed cost was the sum of costs paid for feed intake times the price of feed per kilogram. Palatability was measured by a panel taste test using HH and Gof beef and analyzed for differences. Environmental impacts were calculated based on 1 kg of Japanese beef yield of CO2 equivalents (eq) and animal end weights at each feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Many Asian consumers prefer moderate amounts of IMF in the meat they purchase, whereas visible fat is unpopular with Western (e.g., Europe, Australia) consumers. The amount of IMF within beef muscle varies widely depending on animal breed or genetics (Barendse, 2014; Hocquette et al , 2014; Widmann et al , 2011), the nutrition system (pasture or grain) (Duckett et al , 2013; Sithyphone et al , 2011; Van Elswyk and McNeill, 2014), animal maturity and weight (Duckett et al , 2014; Frank et al , 2016), primal (Pavan and Duckett, 2013) and other factors. Marbling describes the small flecks of visible fat deposited between individual muscle fiber bundles.…”
Section: Introductionmentioning
confidence: 99%
“…Many Asian consumers prefer moderate amounts of IMF in the meat they purchase, whereas visible fat is unpopular with Western (e.g., Europe, Australia) consumers. The amount of IMF within beef muscle varies widely depending on animal breed or genetics (Barendse, 2014; Hocquette et al , 2014; Widmann et al , 2011), the nutrition system (pasture or grain) (Duckett et al , 2013; Sithyphone et al , 2011; Van Elswyk and McNeill, 2014), animal maturity and weight (Duckett et al , 2014; Frank et al , 2016), primal (Pavan and Duckett, 2013) and other factors. Marbling describes the small flecks of visible fat deposited between individual muscle fiber bundles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in rural areas of Japan, such as in the study area included in the current study (the Osumi Peninsula, Kagoshima Prefecture, Japan), most of the breeding beef cattle herds are fed hays collected from their home pastureland. Recently, the importance of this beef-forage production system of Japanese Black cattle has been re-recognized, because it contributes to improved nutrient utilization (ecological aspect) and reduced cost of commercial feeds (economical aspect) [17,20]. However, no evaluative study has been conducted to investigate the nutritional adequacy of forage collected from the home pastureland.…”
mentioning
confidence: 99%
“…Usually this EW strategy involves maintaining a high concentrate diet for a short period before allowing the cows to forage freely in the fields. The EW strategy has been successfully used for Japanese Black cattle (Sithyphone et al, 2011). According to Moriel et al (2014b), steers fed high-concentrate diets at 177 vs. 213 days of age showed larger marbling scores.…”
Section: Introductionmentioning
confidence: 99%
“…Supplying appropriate nutrition can enhance the calf's performance during early life and consequently, improve the production limit providing distinctive opportunities to optimize feeding strategies and increase the profitability of beef cattle production. Some studies have already suggested that exposure to high grain diets for early weaned (EW) calves leads to greater fat deposition and increased marbling scores and carcass quality at slaughter (Myers et al, 1999a, Myers et al, 1999bSithyphone et al, 2011;Moriel et al, 2014aMoriel et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%